FOREWORD FROM HANDLING EDITOR - 11TH EDITION - Sodri, Ahyahudin (Journal of Environmental Science and Sustainable Development, 2023)
We are delighted to present the 11th edition of JESSD, published in December 2023. We have selected twelve of the best articles for this edition that related with topic of Environmental Science and Sustainable Development.